(untitled) (Stato, Chiese e pluralismo confessionale, 2022)
SOMMARIO: 1. Introduzione: dichiarazione d’intenti, obiettivo e metodo - 2. L’assenza di una costituzione nella Chiesa e problematica connessa - 3. L’ordinamento canonico e i suoi limiti nella tutela dei diritti individuali - 4. Un esempio paradigmatico: il processo per l’imposizion Canonical criminal procedural law related to the principle of self-defense: a comparative analysis ABSTRACT: The article compiles an analysis of canonical criminal procedural law tracing it in the first place to the lack, in the canonical system, of a constitutional law, which Paul VI had deemed necessary to be adopted when, in the aftermath of Vatican Council II, he decided to promote that Lex Ecclesiae Fundamentalis, later abandoned under the pontificate of John Paul II. The work makes use of a comparative analysis with Italian criminal procedural law and compares the procedural institutes of one and the other legal system to help understand the breadth and consistency of the gaps and shortcomings of canonical procedural law.e di un decreto penale.